Toxicity and Disease-Related Outcomes after Radiotherapy for Head and Neck Cancer in Human Immunodeficiency Virus-Positive Patients - Grew, David J.; Cooper, Benjamin T.; Nguy, Susanna; Halperin, Jason; Sanfilippo, Nicholas J. (Frontiers in Oncology, 2014)
Background: Human immunodeficiency virus (HIV) seropositivity may be associated with higher risk of local recurrence and poor survival in multiple malignancies. However, long-term disease control in HIV-positive patients with head and neck cancer (HNC) is not well described. The purpose of this study is to review the disease-related outcomes of HIV-positive patients who underwent radiotherapy (RT) or chemoradiotherapy (CRT) at our institution. Methods: We retrospectively reviewed 24 HIV-positive patients who underwent RT for HNC between 2004 and 2013. Patient characteristics, treatment details, and outcomes were collected. Overall survival (OS) and local recurrence-free survival (LRFS) were investigated. Kaplan–Meier estimated survival was calculated. Results: Median follow-up was 21 months. All patients were treated with curative intent. Eighty-three percent had stage III–IV. Primary sites of disease included oropharynx (n = 12), larynx (n = 6), oral cavity (n = 2), unknown primary (n = 2), nasal cavity (n = 1), and paranasal sinuses (n = 1). Four patients (17%) had definitive RT alone and nine had definitive CRT (38%; eight cisplatin and one cetuximab). Eleven (46%) were treated in the adjuvant setting after surgical resection; six with RT alone and five with concurrent cisplatin. Eight patients had acute Grade 3 toxicity with no acute Grade 4 or 5 toxicities. Fifteen patients (63%) were alive and disease-free. Two- and 5-year OS was 67 and 59%, respectively. LRFS at 2-years was 82%. Median OS was 83 months. Conclusion: In this cohort, HIV-positive patients treated aggressively with curative intent had excellent OS and local control following RT or CRT for HNC compared to historical controls. Treatment was relatively well tolerated. This group of patients should be managed aggressively with intent to cure.